2004
DOI: 10.1073/pnas.0400794101
|View full text |Cite
|
Sign up to set email alerts
|

Substance P in the medial amygdala: Emotional stress-sensitive release and modulation of anxiety-related behavior in rats

Abstract: Increasing evidence implicates the substance P (SP)͞neurokinin-1 receptor system in anxiety and depression. However, it is not known whether emotional stimulation alters endogenous extracellular SP levels in brain areas important for processing of anxiety and mood, a prerequisite for a contribution of this neuropeptide system in modulating these behaviors. Therefore, we examined in rats whether the release of SP is sensitive to emotional stressors in distinct subregions of the amygdala, a key area in processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
178
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(189 citation statements)
references
References 63 publications
(65 reference statements)
9
178
0
2
Order By: Relevance
“…Ebner et al (2004) showed that immobilization stress caused a significant increase in SP release within the MeA but not the CeA. They also found that intra-MeA SP infusions produced anxiety-like behaviors as assessed with elevated plus maze, an effect similar to that induced by immobilization.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Ebner et al (2004) showed that immobilization stress caused a significant increase in SP release within the MeA but not the CeA. They also found that intra-MeA SP infusions produced anxiety-like behaviors as assessed with elevated plus maze, an effect similar to that induced by immobilization.…”
Section: Discussionmentioning
confidence: 62%
“…These expression patterns suggest a differential involvement of amygdaloid nuclei in SP-mediated affective behaviors. In fact, increases in SP mRNA and SP release induced by emotional stressors have been found in the MeA, but not in the CeA (Ebner et al, 2004;Sergeyev et al, 2005), and an increase in SP receptor internalization, a marker of SP release, was found in the BLA (Kramer et al, 1998;Smith et al, 1999). Direct infusion of SP into the MeA was shown to be anxiogenic in the elevated plus maze test (Ebner et al, 2004), and infusion of an SP receptor antagonist into the BLA blocked maternal separation-induced vocalization (Boyce et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated platform, 12 Â 12 cm at a height of 70 cm above floor level, located in the middle of a small closet-like room (adapted from Maroun and Richter-Levin, 2003). Similar elevated platform protocols affected the stressresponse mechanisms of adult rats (Degroot et al, 2004;Ebner et al, 2004). Day 3 (aged 29 days) Foot-shock or restraint stressors: rats were randomly subjected to a short foot-shock session or to 2 hours of restraint.…”
Section: 'Juvenile Stress' Proceduresmentioning
confidence: 99%
“…Because NK1 receptors display considerable divergence between species, NK1R antagonists developed for activity at the human NK1R may possess limited efficacy in rat studies (Leffler et al, 2009). We therefore used L822429, a brain-penetrant NK1R antagonist with high affinity for the rat NK1R that produces anxiolytic-like effects after systemic administration (Ebner et al, 2004;Ebner et al, 2008;Singewald et al, 2008). We examined the effects of L822429 on heroin self-administration in short (ShA; 1 h per day) and long access (LgA; 12 h per day) rats.…”
Section: Introductionmentioning
confidence: 99%